Efektivitas implementasi pendidikan anti korupsi di perguruan tinggi dan pengaruhnya terhadap pembentukan karakter mahasiswa - Laila Zulfa, Anis Rahimatul (Maliki Interdisciplinary Journal, 2026)
Corruption in Indonesia has reached a worrying level, as reflected from the data that reveals that the majority of the perpetrators are university graduates. This phenomenon emphasizes the urgency of the strategic role of higher education institutions in preventing it through Anti-Corruption Education (PAK). This research specifically examines the effectiveness of PAK implementation in the university environment, along with its impact on the formation of student character and integrity. With a literature study approach based on descriptive analysis, this study examines literature related to the internalization of anti-corruption values in depth. The main findings underline that PAK goes beyond just the delivery of theory; it is a holistic process of character formation that integrates value and moral education. The success of the implementation depends on the integration into the course curriculum, socialization activities, seminars, and the development of a campus culture that upholds integrity. Core principles such as honesty, empathy, independence, discipline, responsibility, work ethic, simplicity, courage, and justice are proven to strengthen the integrity of individual students. This mature character, in turn, places students as active change agents in efforts to eradicate corruption in society. Overall, this study confirms the substantial influence of PAK in protecting students from corrupt practices, as well as laying a solid ethical foundation for the progress of the nation.